Isolation of Brucella Melitensis and Evaluation of Serum Biochemical Changes in Camels: A Pilot Study to Prevent Human Brucellosis: Life Sciences-Biochemical - Manivannan, Kavitha; Ramasamy, Malathi; Sundaresan, Uma; Duraikannu, Sivakumar (International Journal of Life Science and Pharma Research, 2022)
Brucellosis is an infectious disease of livestock animals, which is reflected as one of the most severe public health issues worldwide. The main aim of this study is to isolate the B.melitensis and to examine the biochemical parameters in the serum of brucella infected and healthy camels. A total of 200 blood samples were collected from the camels of Shahaniya Governorate, Qatar. The Brucella isolation was done using different bacterial growth techniques. The status of blood metabolites and hepatic marker enzyme activities, kidney function markers, and mineral contents were estimated in the serum samples. Our findings revealed the probability of B.melitensis growth with 93-98%. The 34-50% of other species such as S.paucimobilis, A.lwoffii, A.salmonicida, and O.ureolytica were also noted in the serum of camels. In biochemical studies, the decreased status of glucose, total protein, albumin, and globulin in the serum of brucella-affected camels. The activities of AST, ALT, ALP, LDH, and GGT were up-regulated in the serum of brucella-infected camels. The levels BUN, creatinine, urea, creatine kinase, and bilirubin were also increased in the serum of brucella-affected camels. The calcium, magnesium, phosphorus, and iron were decreased in the brucella-infected camels. Here, we found the 93-98% probability of B.melitensis growth in the blood samples of camels. Furthermore, Brucella infection adversely altered the blood metabolites, liver function marker enzyme activities, kidney function markers, and mineral contents in the serum of camels.